Endemic and epidemic bovine neosporosis: description of two events in beef cattle - Calandra, Patricio (2014)
The aim of this study was to describe two events in which Neospora caninum was involved in bovine abortions in beef cattle. In the first event, 11 abortions in 57 heifers were recorded in 45 days. One aborted heifer was 5 times more likely to be seropositive than a non-aborted heifer (OR=4.9; IC 1.2-19.9) (p<0.05). In the second event, no association between serological results and abortions were observed (OR=0,69; 0,06-7,31) (p>0.05). Neither antibodies nor isolation of other pathogens were achieved in any case. On the contrary, antibodies and pathognomonic histopathological lesions were observed in the four fetuses from both cases. Interestingly, the findings in the first event suggest the epidemic behavior of the disease. In contrast, in the second event it appears that few abortions were due to N. caninum, suggesting the presence of endemic neosporosis.